Analysis of Relationship of Employees Payment and Employees Satisfaction at Ballarpur Industries Limited: Examining the Relationship Between Payment and Satisfaction in Employees at Ballarpur Industries Limited (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The present study is focused to examine the relationshipof employees payment and employees satisfaction. The study explains that thepayment system is managed with a computerized system called payroll system.Employees are paid salary after adjusting for deductions and allowances. Modeof payment is bank. Attendance for complete month is calculated on 25 of everymonth with left days attendance is assumed. The problem in the existing systemis the preparation of revised attendance due to assumed attendance. Employeespayments have two main components- Direct and Indirect payments in the form ofwages, salaries, incentives, commissions, and bonuses, and there are indirectpayments in the form of financial benefits like employer-paid insurance andvacations.